Effect of Vertical Irregularity(Lower level) of 5-Storey Laboratory Steel Tower using Modal Parameters - Azhar, Afif Aiman; Kamarudin, Ahmad Fahmy (Recent Trends in Civil Engineering and Built Environment, 2021)
Building multi-story high-rise structure buildings is now common with incredibly limited areas, as open floor structures are by far the most common type of urban architecture. Vertical irregularity is frequently used by designers around the world to place car parks, swimming pools or outdoor areas as it strengthens the buildings' architectural values. A modal analysis then be carried out using STAAD Pro to evaluate the natural frequency nd mode shapes of a 5-storey steel tower model which based on a real steel tower installed at the UTHM Jamilus Research Centre. Based on the previous laboratory findings performed using accelerometer sensors and EFDD analysis, the modal analysis output was verified. 4 parametric studies were performed using STAAD Pro modal analysis to establish vertical irregularities by eliminating the beams at the lower level of the steel tower model. The natural frequency of the bare frame steel tower were f1=f2=5.55Hz and f3=7.21 Hz with the comparable difference of less than 10% compare to Faizul(2019). The steel tower experienced translation on mode 1 and 2 while torsional on mode 3.